Plastic waste aggregate for partial replacement of natural aggregate in asphaltic concrete wearing 20 in hot mix asphalt - Ahmad Kamal Akram Md. Uzir, 1994-, author; Md. Maniruzzaman A. Aziz, supervisor; Fakulti Kejuruteraan Awam (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper (Sarjana Muda Kejuruteraan (Awam)) - Universiti Teknologi Malaysia, 2017